Influence of Ramadan fasting on physiological and performance variables in football players: Summary of the F-MARC 2006 Ramadan fasting study - Zerguini, Y.; Dvorak, J.; Maughan, R. J.; Leiper, J. B.; Bartagi, Z.; Kirkendall, D. T.; Al-Riyami, M.; Junge, A. (Journal of Sports Sciences, 2008)
The timing of food and liquid intake depends on the times of sunset and sunrise during the month of Ramadan. The current body of knowledge presents contradicting results as to the effect of Ramadan fasting on body mass, body composition and metabolic changes. The main objective of the present investigation was to gain additional information and scientific data in conformity with the philosophical background of Islam to allow optimisation of the daily training and dietary regimen in relation to the mental and physical performance of football players. The four teams, along with their coaches and trainers, attended a residential training camp at training centre 3 weeks before the start of Ramadan and throughout the study. Energy intake was relatively stable in the fasting group, but there was a small, albeit significant, decrease of approximately 0.7 kg in body mass. Water intake increased on average by 1.3 l/day in line with the greater energy intake in the non-fasting group in Ramadan. Daily sodium intake fell during Ramadan in the fasting players but increased slightly in the non-fasting group. Fasting players trained on average 11 h after their last food and drink, and reported that they felt slightly less ready to train during the Ramadan fast. None of the assessed performance variables was negatively affected by fasting while nearly all variables showed significant improvement at the third test session, indicating a training effect. Heart rate measurements in one training session during the third week of Ramadan appeared to suggest that the training load during training was marginally greater for the fasting than for the non-fasting players. However, the overall exercise load measures indicated that there was no biologically significant difference between the fasting and non-fasting groups.